(untitled) (Al-Academy, 2017)
The sculpture composing of iron materials is being considered most important raw material that has been used by the modern artist ,especially period of post –modernism. The works of the two artists ( SALIH AL-QARAGHULI and AHMED AL-BAHRANI) the most important works that entailed to be studied for being using iron material in most of their sculpturing works; in works of Al-Quraghuli, we find ores composing of iron wires , animals threads and remaining of trash and to be assembled in a sculptured text with unique style in Arab Home. Moreover, we find huge works of (al-Bahrani) represented into formations characterized with its ironic flexibility, its abstracted engineering forms. Al-Bahrani solely has used iron plates represented in its sole structure. The subject of research aims at knowing the method of bringing out ore of sculpture and how to embody it as consisting of iron material ; besides , the benefit of the research for blocking the gap in arts of plastics , especially in field of sculpture , since there has not been former study in this respect. The first approach consists of iron ore in the Modern European sculpture and how to functionalize it in the sculpture ; besides , the sources from which has been emerged. Quoting set of arts works giving obvious indications about how to use this material in sculpture field. The second approach depicts artistic trends in the sculptures each of ( Salah and Ahmed) who are the bases of the mater –subject of the research.. This research summarizes initials and sources that both being affected , in addition to their influence in the most modern works and post- modern works by reciting some European works that embody the iron material besides expressing its influence in European works. Then , the artistic influences by mentioning some of his collective works , especially the iron , after then, the research focuses on initials ( Ahmed Al-Bahrani) and his solely artistic distinguishing style In Arab Home. Thus, the research (third chapter) sheds light on procedures in its accurate picture, then it sets off to analyses the symbols chosen on purpose. The researcher has believed that this aspect will achieve the purposes by choosing two samples for each one, by depending on indication that resulted into samples analysis. Then , the fourth chapter aims at accomplishing results concentrated around the samples , then conclusions that have been concluded from the study, then recommendations an suggestions since being regarded as an important one in the research